Cross-cultural communication competence of students in the unique context of the Polish–Czech borderland - Michał Szyszka; Megan Hopkins; Joanna Kurowska-Pysz; Edyta Nowak-Żółty; Dominik Krężołek (Multidisciplinary Journal of School Education)
Research objectives (aims) and problem(s): The aim of this study was to identify differences in the level and determinants of intercultural communication competence among school pupils in the Polish–Czech border  region. Specifically, we sought to determine whether statistically significant differences exist among the study groups, and which variables—such as environment, gender, faith, national identity, and community affiliation—shape intercultural communication skills.